An updated account of overgeneral autobiographical memory in depression. (June 2023) - Weiss-Cowie, Samuel; Verhaeghen, Paul; Duarte, Audrey
Abstract: Previous meta-analyses on Overgeneral Autobiographical Memory (OGM) and depression have emphasised clinically diagnosed current depression, leaving questions about subthreshold and remitted depression. Further, numerous studies of OGM remain unconsidered due to a focus on one testing paradigm, the Autobiographical Memory Test (AMT). We conducted a meta-analysis on OGM in depression including remitted, subthreshold, and currently depressed samples and incorporating non-AMT studies. Our novel use of three-level models enabled robust variance analyses with multiple effect sizes from each study while controlling for dependencies across effect sizes. With results from 67 published and unpublished works, ours is the largest meta-analysis to date on OGM in depression. We identified decreased autobiographical memory specificity (Hedges' g = −0.73) and increased categoricity (Hedges' g = 0.77) for depressed individuals over controls. Moderator analyses suggested more severe OGM in current, clinical MDD than subthreshold and remitted depression, although deficits were still present in the latter groups. Our results highlight the importance of utilising a broader range of testing paradigms and considering non-clinical depression in future work. Highlights: Largest meta-analysis to date on overgeneral autobiographical memory in depression. Depression linked to lower memory specificity and higher categoricity. Deficits less severe for those with subthreshold and remitted depression. Overgeneral autobiographical memory equally apparent for all valences.